2003
DOI: 10.1038/sj.ejcn.1601703
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplement decreases the homocysteine increasing effect of filtered coffee. A randomised placebo-controlled study

Abstract: Objective: Elevated levels of plasma total homocysteine (tHcy) are identified as independent risk factors for coronary heart disease and for fetal neural tube defects. tHcy levels are negatively associated with folic acid, pyridoxine and cobalamine, and positively associated with coffee consumption and smoking. A total of 600 ml of filtered coffee results in a tHcy increase that 200 mg of folic acid or 40 mg of pyridoxine supplementation might eliminate. Design: Randomised, blinded study with two consecutive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
11
0
3
Order By: Relevance
“…Another study by the same group (10 ) suggested that the additional rise in homocysteine for coffee drinkers could be due to the chlorogenic acid content of coffee, perhaps through its metabolism by methylation, which leads to increased homocysteine production (40 ). Both of these mechanisms are compatible with the observation that folate supplementation prevented the increase in tHcy following coffee consumption (11 ).…”
Section: The Increase In Thcysupporting
confidence: 68%
See 1 more Smart Citation
“…Another study by the same group (10 ) suggested that the additional rise in homocysteine for coffee drinkers could be due to the chlorogenic acid content of coffee, perhaps through its metabolism by methylation, which leads to increased homocysteine production (40 ). Both of these mechanisms are compatible with the observation that folate supplementation prevented the increase in tHcy following coffee consumption (11 ).…”
Section: The Increase In Thcysupporting
confidence: 68%
“…Thus, the mechanism behind the tHcy increase is uncertain, although caffeine, as well as chlorogenic acid, a polyphenol found in large quantities in coffee, were shown to increase tHcy (8,10 ). Moreover, the addition of 200 g/day of folic acid to coffee intervention groups prevented the increase in tHcy (11 ).…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…However, the effects of some of the lifestyle factors have been confirmed in randomized controlled trials (van der Gaag et al, 2000;Stein et al, 2002;Strandhagen et al, 2003), although not in all (Wright et al, 1998;Bleich et al, 2001;Tonstad and Urdal, 2002;Duncan et al, 2004;Beulens et al, 2005). Especially the results from trials examining the Simple regression models were adjusted for follow-up time, baseline values of homocysteine, and baseline value of the biological marker.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusting for different possible confounders did not alter the result. The study by Strandhagen et al also showed that 4 cups of filtered coffee had an effect on plasma homocysteine, by 1 mmol l (1 (96). Until recently, no plausible mechanism was known to explain the homocysteine-raising effect of coffee, but a recent observational study showed a positive association between caffeine intake and homocysteine concentrations (90).…”
Section: Coffee and Serum Cholesterolmentioning
confidence: 99%